Is There a Self-fulfilling Prophecy in Credit Rating Announcements? - Carvalho, P.; Laux, P.; Pereira, J. (2014 FMA Annual Meeting, 2014)
Although credit ratings are meant to foretell a firm’s risk of default, anecdotal evidence suggests that they actually influence the firm’s probability of default. This paper reports systematic evidence on some unintended effects of rating downgrades on future credit defaults. Based on complementary causality methodologies and using an extensive database of long-term corporate obligation ratings issued by Moody’s, S&P and Fitch, from 1990 to 2012, the paper shows that downgrades crossing the threshold between investment grade and speculative grade may cause an increase of at least 3% in the 1-year probability of default. The increase in the probability of default seems to be stronger for deeper rating downgrades. The effect is also likely to be stronger for firms that already have a low initial rating.